Ehrlichia chaffeensis EplA Interaction With Host Cell Protein Disulfide Isomerase Promotes Infection - Green, Ryan S.; Izac, Jerilyn R.; Naimi, Waheeda A.; O'Bier, Nathaniel; Breitschwerdt, Edward B.; Marconi, Richard T.; Carlyon, Jason A. (Frontiers in Cellular and Infection Microbiology, 2020)
Ehrlichia chaffeensis is an obligate intracellular bacterium that invades monocytes to cause the emerging and potentially severe disease, monocytic ehrlichiosis. Ehrlichial invasion of host cells, a process that is essential for the bacterium's survival and pathogenesis, is incompletely understood. In this study, we identified ECH_0377, henceforth designated as EplA (E. chaffeensis PDI ligand A) as an E. chaffeensis adhesin that interacts with host cell protein disulfide isomerase (PDI) to mediate bacterial entry into host cells. EplA is an outer membrane protein that E. chaffeensis expresses during growth in THP-1 monocytic cells. Canine sera confirmed to be positive for exposure to Ehrlichia spp. recognized recombinant EplA, indicating that it is expressed during infection in vivo. EplA antiserum inhibited the bacterium's ability to infect monocytic cells. The EplA-PDI interaction was confirmed via co-immunoprecipitation. Treating host cell surfaces with antibodies that inhibit PDI and/or thioredoxin-1 thiol reductase activity impaired E. chaffeensis infection. Chemical reduction of host cell surfaces, but not bacterial surfaces with tris(2-carboxyethyl)phosphine (TCEP) restored ehrlichial infectivity in the presence of the PDI-neutralizing antibody. Antisera specific for EplA C-terminal residues 95-104 (EplA95-104) or outer membrane protein A amino acids 53-68 (OmpA53-68) reduced E. chaffeensis infection of THP-1 cells. Notably, TCEP rescued ehrlichial infectivity of bacteria that had been treated with anti-EplA95-104, but not anti-EcOmpA53-68. These results demonstrate that EplA contributes to E. chaffeensis infection of monocytic cells by engaging PDI and exploiting the enzyme's reduction of host cell surface disulfide bonds in an EplA C-terminus-dependent manner and identify EplA95-104 and EcOmpA53-68 as novel ehrlichial receptor binding domains.